Mixed convection casson fluids with the effects of porosity and radiation - Nur Fatihah, Mod Omar; Zulkhibri, Ismail; Rahimah, Jusoh; Rozaimi, Abu Samah; Husna Izzati, Osman; Ahmad Qushairi, Mohamad (Penerbit UMP, 2022)
The analysis of mixed convection Casson fluid with the e ffect of porosity and radiation was conducted. The governing p artial d ifferential e quations (PDE) in dimensional form were formulated with associated initial and boundary conditions. The PDE were transformed intodimensionless form by presenting suitable non-dimensional variables. The temperature and velocity profiles were obtained by employing the method of Laplace transform, to ensure that initial and boundary conditions involved were satisfied. The graphical representation illustrates the effects of parameters for Casson fluid, porous medium and Grashof (Gr) number, in addition toradiation. It is inferred that at the start, the velocity decreases. However, at some point the velocity rises when the Casson parameter increases. Additionally, the increasing of radiation and Grashof number has influenced the velocity to increase.